Does Profitability Mediate The Effect Of Intellectual Capital And Financial Leverage On Firm Value Of Banking Companies In Indonesia? - Aryanie, Irne; Arfan, Muhammad; Islahuddin, Islahuddin (Universitas Teuku Umar, 2023)
The objective of this study is to examine wether profitability mediate the effect of intellectual capital and financial leverage on the firm value. The population of this study are 143 banking companies listed on the Indonesia Stock Exchange from 2013 to 2016. This study is a census method because all elements of population are studied, so to test the hypotheses does not use a significant test. Conclusions are drawn directly from the coefficient values of each variable. Data are collected from annual reports and analyzed by using path analysis. This study incorporates profitability as a mediating variable in the research model, which was not examined in previous studies. The results indicate that intellectual capital and financial leverage have positive effects on firm value and profitability can mediate the effect of intellectual capital and financial leverage on the firm value.